Answer :


Ideas required to solve the problem:


The general solution of any trigonometric equation is given as –


• sin x = sin y, implies x = nπ + (– 1)ny, where n Z.


• cos x = cos y, implies x = 2nπ ± y, where n Z.


• tan x = tan y, implies x = nπ + y, where n Z.


Given,


sin 2x - sin 4x + sin 6x = 0


To solve the equation we need to change its form so that we can equate the t-ratios individually.


For this we will be applying transformation formulae. While applying the


Transformation formula we need to select the terms wisely which we want


to transform.


we have, sin 2x - sin 4x + sin 6x = 0


we will use sin 6x and sin 2x for transformation as after transformation it will give sin 4x term which can be taken common.


{ sin A + sin B =


-sin 4x + 2 sin


2sin 4x cos 2x – sin 4x = 0


sin 4x ( 2cos 2x – 1) = 0


either, sin 4x = 0 or 2cos 2x – 1 = 0


sin 4x = sin 0 or cos 2x = � = cos π/3


If sin x = sin y, implies x = nπ + (– 1)n y, where n Z.


If cos x = cos y, implies x = 2nπ ± y, where n Z.


Comparing obtained equation with standard equation, we have:


4x = nπ or 2x = 2mπ ± π/3


where m,n ϵ Z ..ans


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve the followiRD Sharma - Mathematics

3sin2 RD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve : <span lanRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve : <span lanRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Find the general RD Sharma - Mathematics

Find the general RS Aggarwal - Mathematics